2013
DOI: 10.1111/pai.12052
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrated egg white: An allergen source for improving efficacy and safety in the diagnosis and treatment for egg allergy

Abstract: This is the first time that it is shown that the allergenicity of commercially available DEW is equivalent to raw egg whites. In vivo and in vitro tests showed that processing of DEW does not affect the allergenicity of egg proteins. DEW is an effective and microbiologically safer source of allergen for the diagnosis of egg allergy. Furthermore, DEW can be used in egg oral immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The different egg preparations (e.g., hard-boiled, scrambled, egg powder) used in challenges may have had different specific protein contents and conformations that could have affected challenge outcomes. Escudero et al 35 showed that the protein composition, allergenicity, and egg food challenge outcomes by using raw versus dehydrated EW were equivalent. It may have been beneficial to perform food challenges to raw egg, but this was beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 99%
“…The different egg preparations (e.g., hard-boiled, scrambled, egg powder) used in challenges may have had different specific protein contents and conformations that could have affected challenge outcomes. Escudero et al 35 showed that the protein composition, allergenicity, and egg food challenge outcomes by using raw versus dehydrated EW were equivalent. It may have been beneficial to perform food challenges to raw egg, but this was beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that the results of skin tests and oral challenges performed to 40 egg-allergic patients demonstrated that OVO-DES maintains the same allergenicity as raw egg white, with no significant differences in the doses that led to symptoms following the positive challenges and in the symptoms observed [10]. This raised the possibility that the presence of papain could increase the allergenic potential of LYS.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the starting dose of EOIT, the patient underwent a double-blind placebo-controlled food challenge (DBPCFC) with dehydrated egg white (OVO-DES NM, Madrid, Spain) [10]. Administration of 8 doses (4, 20, 50, 110, 225, 450, 900 and 1,800 mg) in 50 ml of soy milk shake with chocolate was scheduled every 20 min (corresponding to an accumulated dose of, approximately, 3,600 mg, equivalent to 43 ml of a whole egg white) until symptom development.…”
Section: Methodsmentioning
confidence: 99%
“…Oral challenges, one performed with raw/pasteurized EW or E and the other with hard‐boiled EW or baked egg, establish the phenotype. The use of pasteurized products to avoid potential risk of infection is supported by studies reporting that they maintained their IgE‐binding capacity or allergenicity . Baked egg‐reactive subjects have larger skin prick test (SPT) wheals and greater EW‐, OVA‐ and OVM‐specific IgE levels than baked egg‐tolerant subjects but with a great deal of overlap .…”
Section: Introductionmentioning
confidence: 99%